Analisis Pengaruh Kualitas Pelayanan, Fasilitas Dan Kemudahan Akses Terhadap Kepuasan Pelanggan Pada Bandar Udara Internasional Jenderal Ahmad Yani Semarang - Reni Kristiani Podengge; Haryani Haryani (Jurnal Manajemen Kreatif dan Inovasi, 2023)
The purpose of this study was to analyze the effect of service quality, facilities and ease of access on customer satisfaction at Jenderal Ahmad Yani International Airport, Semarang. The population is all customers who travel through Jenderal Ahmad Yani International Airport, Semarang. The sample in this study used probability sampling, with a total sample of 100 respondents.The results showed that service quality had a significant positive effect on customer satisfaction (t count = 5.201 > t table = 1.658 and a significance number = 0.000 <  = 0.05). Thus, the hypothesis (H1) is that service quality has a positive effect on customer satisfaction. Facilities have a significant positive effect on customer satisfaction (t count = 2.653 > t table = 1.658 and a significance number = 0.009 <  = 0.05). Thus, the hypothesis (H2) is that facilities have a positive effect on customer satisfaction. Ease of access has a significant positive effect on customer satisfaction (t count = 3.206 > t table = 1.658 and a significance number = 0.002 <  = 0.05). Thus, the hypothesis (H3) is that ease of access has a positive effect on customer satisfaction.The regression coefficient β1 = 0.432, (signed positive) means that the better the service quality, the higher the customer satisfaction. The regression coefficient β2 = 0.222, (signed positive) means that the better the facilities provided, the higher the customer satisfaction. The regression coefficient β3 = 0.264 (signed positive) means that if the ease of access is good, the customer satisfaction will be higher at Jenderal Ahmad Yani Airport, Semarang.